2014
DOI: 10.1007/s11999-013-3394-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher Charlson Comorbidity Index Scores are Associated With Readmission After Orthopaedic Surgery

Abstract: Background The Charlson Comorbidity Index (CCI) originally was developed to predict mortality within 1 year of hospital admission in patients without trauma. As it includes factors associated with medical and surgical complexities, it also may be useful as a predictive tool for hospital readmission after orthopaedic surgery, but to our knowledge, this has not been studied. Questions/purposes We asked whether an increased score on the CCI was associated with (1) readmission, (2) an increased risk of surgical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 39 publications
5
93
2
2
Order By: Relevance
“…This index provides a score ranging from 0 to 24 with a higher score representing more severe comorbidity status based on 12 weighted comorbidities (congestive heart failure, dementia, chronic pulmonary disease, rheumatologic disease, mild liver disease, diabetes with chronic complications, hemiplegia or paraplegia, renal disease, any malignancy, moderate or severe liver disease, metastatic solid tumor, and HIV/ AIDS). We determined the modified Charlson Comorbidity Index through a previously described algorithm based on ICD-9 codes given before the day of surgery [6,30,38] (Appendix 2. Supplemental material is available with the online version of CORR 1 .).…”
Section: Methodsmentioning
confidence: 99%
“…This index provides a score ranging from 0 to 24 with a higher score representing more severe comorbidity status based on 12 weighted comorbidities (congestive heart failure, dementia, chronic pulmonary disease, rheumatologic disease, mild liver disease, diabetes with chronic complications, hemiplegia or paraplegia, renal disease, any malignancy, moderate or severe liver disease, metastatic solid tumor, and HIV/ AIDS). We determined the modified Charlson Comorbidity Index through a previously described algorithm based on ICD-9 codes given before the day of surgery [6,30,38] (Appendix 2. Supplemental material is available with the online version of CORR 1 .).…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative risk assessment can help with decision-making and management strategies [11,37,50]. Several models for estimating risk based on coded comorbidities are currently in use for orthopaedic patients, but there is no consensus regarding the optimal approach [22,37,49,51,56,57]. Selecting appropriate risk adjustment models can help hospitals contain costs while ensuring high levels of quality.…”
Section: Introductionmentioning
confidence: 99%
“…Although many scoring systems have been desig- ned for hip fractures, CCI seems to be the frequently used in the prediction of mortality following fracture surgery 7,9,20,21 . In a study by Kirkland et al, 22 on hip fractures in elderly patients, a strong relationship was found between a CCI score of >6 and 30-day mortality rates but no comment was made about sensitivity or specificity of CCI scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several scoring methods have been created taking comorbid factors into consideration, which would be of benefit in the prediction of mortality. The Charlson Comorbidity Index (CCI) and the American Society of Anaesthesiologists score (ASA) have been widely used in the prediction of mortality 1,7,[9][10][11] . Although many scoring systems have been described in the literature, the perfect risk model for predicting mortality following hip fracture surgery does not exist, and research on the subject is ongoing 12 .…”
Section: öZmentioning
confidence: 99%